Osteophyte formation causes neurological symptoms after anterior cervical discectomy and fusion (ACDF): A case report - Jin, Haiming; Luo, Jiangtao; Jiang, Yuhan; Lin, Jinghao; Jiang, Junchen; Ren, Rufeng; Fang, Weiyuan; Wu, Yaosen; Wang, Xiangyang (Frontiers in Surgery, 2023)
The occurrence of osteophytes following intervertebral disc degeneration in clinical practice has attracted the attention of spinal surgeons. However, the occurrence of osteophytes, especially osteophyte formation in the spinal canal, after anterior cervical discectomy and fusion (ACDF) is rarely reported. We reported a 42-year-old male patient who underwent C4-6 ACDF in another public hospital in the province two years prior due to cervical stenosis. His primary symptoms were significantly relieved, but he developed new pain and weakness of the right leg over the six months after the surgery. The imaging results showed a prominent posterior osteophyte at the level of C5/6, which compressed the spinal cord anteriorly. Accordingly, we performed cervical open-door laminoplasty to decompress the spinal cord. At the one-year follow-up, the patient’s clinical symptoms were markedly improved. Therefore, the aim of this case study is to make surgeons aware that a severe intracanal osteophyte can also develop at the operated level after ACDF, and careful, regular follow-ups are warranted. More attention should pay to thoroughly removal of osteophytes and strong fixation at the operated level during ACDF, which may reduce the incidence of new osteophyte. In addition, surgical interventions may be needed.